A COMPREHENSIVE STUDY OF THE PERIPHERAL BLOOD OF PRIMARY CERVICAL CANCER PATIENTS - Domina, E.A.; Glavin, O.A.; Makovetska, L.I.; Mikhailenko, V.M. (Reports of the National Academy of Sciences of Ukraine, 2024)
Cervical cancer stands out as one of the most prevalent pathologies in the spectrum of oncological morbidity among the female population in Ukraine. Oxidative stress plays a significant role in the development and progression of this disease. During radiation therapy, normal cells are exposed to radiation, potentially leading to the emergence of distant complications. Several biological indicators reflecting the state of oxidative processes in peripheral blood, along with the level of DNA damage and lymphocyte apoptosis, were determined in patients prior to the initiation of therapy and compared with a control group. The development of oxidative stress was evidenced by a 1.8-fold increase in the generation of the superoxide anion radical in lymphocytes, a 1.4-fold increase in the pro-antioxidant ratio in blood, and a 1.6-fold decrease in the content of sulfhydryl groups of proteins in plasma. In lymphocytes, these changes were accompanied by a 1.8-fold decrease in the transmembrane potential of mitochondria and a 2.1- fold increase in the level of DNA double-strand breaks and a 3.5-fold increase in apoptosis. An inverse correlation was established between the total production of free radicals and the generation of the superoxide anion in lymphocytes, indicating its crucial role in damaging these cells in cervical cancer patients. The data obtained will serve as a baseline for determining radiation-induced changes in healthy cells within the tumor environment postradiotherapy.